2022
DOI: 10.1111/sjop.12836
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in the induction and regulation of the negative emotions fear and disgust: A functional near infrared spectroscopy study

Abstract: Affective processing, including induction and regulation of emotion, activates neural networks, induces physiological responses, and generates subjective experience. Dysregulation of these processes can lead to maladaptive behavior and even psychiatric morbidity. Multimodal studies of emotion thus not only help elucidate the nature of emotion, but also contribute to important clinical insights. In the present study, we compared the induction (EI) and effortful regulation (ER) with reappraisal of fear and disgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 139 publications
3
4
0
Order By: Relevance
“…Previous studies have also shown physiological differences in the autonomic responses fear and disgust elicit ( 7 , 8 , 76 , 77 ). Consistent with this, we found in a previous study ( 61 ) significant differences in EDR frequency during emotion induction of fear and disgust, reflecting increased sympathetic activity during fear but not disgust. This difference in EDR frequency between fear and disgust was replicated in the current study in the placebo arm but was abolished by escitalopram.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies have also shown physiological differences in the autonomic responses fear and disgust elicit ( 7 , 8 , 76 , 77 ). Consistent with this, we found in a previous study ( 61 ) significant differences in EDR frequency during emotion induction of fear and disgust, reflecting increased sympathetic activity during fear but not disgust. This difference in EDR frequency between fear and disgust was replicated in the current study in the placebo arm but was abolished by escitalopram.…”
Section: Discussionsupporting
confidence: 91%
“…(A,B) The dotted line comparisons in A (fear) and B (disgust) show that compared to control phase, after ingestion of escitalopram, a roughly 30% increase in electrodermal response frequency was measured at rest (absence of emotive stimuli) during the fear experiments but not the disgust ones. (A–D) The solid line comparisons show that, similarly to what was previously reported in a study without pharmacological intervention ( 61 ), placebo was associated with no difference between task EDA and rest in fear (A,C) but lower than rest in disgust (B,D) . This pattern was reversed in the escitalopram arm, where task EDA was significantly lower than rest in fear (A,C) but not significantly different than rest in disgust (B,D) .…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations